Enforcement of Labor Regulation and the Labor Market Effects of Trade: Evidence from Brazil - Gabriel Ulyssea; Vladimir Ponczek (Institute of Labor Economics (IZA), 2018)
How does enforcement of labor regulations shape the labor market effects of trade? To tackle this question, we exploit the Brazilian trade liberalization episode and exogenous variation in the intensity of both the trade shock and enforcement across local labor markets. Regions with stricter enforcement observed no increase in informal employment but large disemployment effects. Regions with weaker enforcement had no employment losses but substantial increases in informality. All effects are concentrated on unskilled workers, with no effects on skilled workers. The results indicate that informality acts as a buffer that reduces trade-induced adjustment costs in the labor market.
Keywords: F16; J46; K31; 330; trade; enforcement of labor regulations; informality